Clinical outcomes of DMEK comparing endothelium-out injector and endothelium-in pull-through techniques in Asian eyes - Cheong, Ezekiel Ze Ken; Ng Yin Ling, Clarissa; Wong, Qiu Ying; Chua, Chloe Si Qi; Htoon, Hla Myint; Ang, Marcus (Frontiers in Medicine, 2025)
This is a prospective interventional study of 180 consecutive Descemet membrane endothelial keratoplasty (DMEK) cases, comparing injector (endothelium-out) and pull-through (endothelium-in) surgical techniques in Asian eyes. The main outcome measures were 5-year graft survival and intraoperative and postoperative complications. In our study, a pull-through technique for DMEK was employed more frequently in PBK (66.2%) than in FECD (10.7%) eyes (p < 0.001). Overall 5-year graft survival was 90% (98% in FECD and 64% in PBK eyes; p < 0.001). We observed higher rates of intraoperative donor graft tears (6.5% vs. 0.8%; p = 0.049) and persistent postoperative corneal edema (19.4% vs. 6.8%; p = 0.022) in pull-through DMEK than injector DMEK. However, multivariable analysis suggested that surgical technique was not a significant factor associated with graft survival, that is, PBK as the surgical indication was the main factor associated with graft failure (hazard ratio = 12.5; p < 0.01) and postoperative complications (odds ratio = 4.41; p < 0.01), regardless of surgical technique used. In our Asian study cohort, both injector (endothelium-out) and pull-through (endothelium-in) surgical techniques for DMEK had comparable clinical outcomes, when adjusted for confounders.